What Is the Sweetest UPR Flavor for the β-cell? That Is the Question - Lenghel, Alina; Gheorghita, Alina Maria; Vacaru, Andrei Mircea; Vacaru, Ana-Maria (Frontiers in Endocrinology, 2021)
Unfolded protein response (UPR) is a mechanism conserved from yeasts to mammals and, based on the generally accepted dogma, helps the secretory performance of a cell, by improving its capacity to cope with a burden in the endoplasmic reticulum (ER). The ER of β-cells, “professional secretory cells”, has to manage tremendous amounts of insulin, which elicits a strong pressure on the ER intrinsic folding capacity. Thus, the constant demand for insulin production results in misfolded proinsulin, triggering a physiological upregulation of UPR to restore homeostasis. Most diabetic disorders are characterized by the loss of functional β-cells, and the pathological side of UPR plays an instrumental role. The transition from a homeostatic to a pathological UPR that ultimately leads to insulin-producing β-cell decay entails complex cellular processes and molecular mechanisms which remain poorly described so far. Here, we summarize important processes that are coupled with or driven by UPR in β-cells, such as proliferation, inflammation and dedifferentiation. We conclude that the UPR comes in different “flavors” and each of them is correlated with a specific outcome for the cell, from survival, differentiation, proliferation as well as cell death. All these greatly depend on the way UPR is triggered, however what exactly is the switch that favors the activation of one UPR as opposed to others is largely unknown. Much work remains to be done to cover the gaps in understanding in this important emerging field as this may help in the constant need to develop novel therapies for diabetes.